Analysis on the Influence of Wind Power Participating in Frequency Modulation on Low-frequency Oscillation in Yunnan Power Grid. Issue 5 (January 2021) - Yang, Lei; Gao, Jingye; Ma, Zun; Huang, Wei; Zhang, Dan; Xing, Chao; Xiang, Chuan; He, Xin
Abstract: Low-frequency oscillation in Yunnan power grid with a high proportion of hydropower units is prominent. With the continuous access of large-scale new energy sources, it poses a serious threat to the frequency stability of the power grid. Based on the simulation model of Yunnan power grid in 2020, this paper studies the effect of wind power participating in frequency modulation on the damping of Yunnan power grid. Several low-frequency oscillation modes in Yunnan power grid are given through the analysis of two typical operation modes of Xia Da and Chun Xiao. This paper also analyzes the effect of the fan on the low-frequency oscillation mode of Yunnan power grid after adding primary frequency modulation and inertial control. The results show that both inertia control of fan and excessive primary FM sag coefficients will reduce the damping of the system. After wind power is involved in frequency modulation, a favorable effect on the damping of the low-frequency oscillation mode of Yunnan power grid can be produced by setting the control parameters appropriately.